Advancements in supersonic flight control: review of cavity flow impact and integration of active and passive control mechanisms - Balakrishnan, Sheysshindth; Abu Talib, Abd. Rahim; Mat, Shabudin; Abdul Hamid, Mohd. Faisal (Penerbit UTM Press, 2024)
This review paper explores the challenges of supersonic flight, specifically focusing on the impact of cavities on flight dynamics and the effectiveness of various control mechanisms. The paper addresses three primary objectives: understanding cavity-induced effects during supersonic flight, evaluating the effectiveness of active and passive cavity flow control techniques, and exploring the integration of both approaches for optimized control. Cavities, or recessed areas on aircraft surfaces, can cause complex shock-wave patterns during supersonic flight, leading to problems like increased drag, reduced controllability, and heightened acoustic emissions. The paper aims to highlight the the mechanisms underlying these cavity-induced phenomena by analyzing existing research and shedding light on their effects on flight dynamics. The effectiveness of two distinct control strategies, active and passive, in managing cavity-related issues is investigated. Active control involves real-time adjustments using technologies like jets and feedback loops, while passive methods alter flow behavior through design features. The review examines the outcomes of research studies that have employed these techniques, providing an assessment of their individual merits and limitations. The paper also emphasizes the potential benefits of integrating active and passive control approaches to achieve a comprehensive solution for cavity-induced instabilities. By combining the strengths of both methods, this integrated approach promises improved stability, reduced drag, and enhanced overall flight performance. The review synthesizes findings from existing research, facilitating a comparison of outcomes, and offering a guide for future investigations into the synergistic application of active and passive controllers.